[tex]\displaystyle{\int\, \dfrac{x^{\frac{1}{3}}\, -\, 3}{x^{\frac{2}{3}}}\, dx}[/tex]

[tex]\displaystyle{=\, \int\, x^{\frac{1}{3}}\, -\, 3\, \dot\, x^{-\frac{2}{3}}\, dx}[/tex]

[tex]\displaystyle{=\, \frac{1}{\left(\frac{4}{3}\right)}x^{\frac{4}{3}} \, -\, 3x\, \dot\, \frac{1}{\left(\frac{1}{3}\right)}x^{\frac{1}{3}}}[/tex]

[tex]\displaystyle{=\, \frac{3x^{\frac{4}{3}}}{4}\, -\, 3x\, \dot\, 3x^{\frac{1}{3}}}[/tex]

[tex]\displaystyle{=\, \frac{3x^{\frac{4}{3}}}{4}\, -\, 3x^{\frac{4}{3}}\, +\, C}[/tex]

## Bookmarks